Survey on Resource Allocation for Future 6G Network Architectures - Conceição, Filipe (2024)
Funding Information: This work is supported by the European Regional Development Fund (FEDER), through the Competitiveness and Internationalization Operational Programme (COMPETE 2020) of the Portugal 2020 framework, Regional OP Centro (POCI-01-0145-FEDER030588), Regional Operational Program of Lisbon (Lisboa-01-0145-FEDER-030588). Publisher Copyright: © 2024 by the authors.